Political risk effects and entry mode strategies of multinational corporations (MNCS) in Nigeria - Olufemi Amos, Akinbola; Taofik Osindero, Agbatogun; Omolola Sariat, Akinbola; SekinatArike, Sanni (Applied Studies in Agribusiness and Commerce, 2021)
Research on the political risk and entry mode of multinational companies (MNCs) has been one of the major subjects of interest in international business terrain, and the political risk factor has constitute a major basis for explaining whether exporting, licensing, franchising, or joint venture agreement (JVA) and Foreign direct investment seems to be appropriate. As such, the study examined the effect of political risk as it affects the entry mode strategies of selected multinational corporations in Nigeria as the economy of most developing economies has been characterized as being exposed to political instability and risk. The research adopted the survey technique with inference to the expo facto method and adopted questionnaire as an instrument through content and test re-test appraisal before data were analyzed through the IBM Statistical Package for the Social Sciences. The results from the analysis indicated that franchising remains a viable option of multinationals in Nigeria and the second hypothesis indicated that licensing significantly reduces the risk exposure of multinational corporations as the licensor have lesser liability in an unstable political economy of the licensee. Based on these findings companies are recommended to adopt appropriate entry strategies in line with governmental policies and economic situation before entering foreign markets.JEL CODES: M1, M10